Two-photon laser printing to mechanically stimulate multicellular systems in 3D - Colombo, Federico; Taale, Mohammadreza; Taheri, Fereydoon; Villiou, Maria; Debatin, Teresa; Dulatahu, Gent; Kollenz, Philipp; Schmidt, Målin; Schlagheck, Christina; Wittbrodt, Joachim; Selhuber-Unkel, Christine (Advanced functional materials, 2024)
Biological activities take place in 3D environments, where cells interact in various directions in a defined, often microstructured, space. A sub-millimeter-sized stretching device is developed to mechanically stimulate a structurally restricted, soft multicellular microenvironment to investigate the effect of defined cyclic mechanical forces on a multicellular system. It consists of a multi-material 3D microstructure made of Polydimethylsiloxane (PDMS) and gelatine-based hydrogel, which is printed using the 2-photon polymerization (2PP) method. The printed structures are first characterized microscopically and mechanically to study the effect of different printing parameters. Using 2PP, organotypic cell cultures are then directly printed into the hydrogel structures to create true 3D cell culture systems. These systems are mechanically stimulated with a cantilever by indenting at defined positions. The cells in the 3D organotypic cell culture change morphology and actin orientation when exposed to cyclic mechanical stretch, even within short timescales of 30 min. As proof of concept, a Medaka retinal organoid is encapsulated in the same structure to demonstrate that even preformed organoids can be stimulated by this method. The results highlight the capability of 2PP for manufacturing multifunctional soft devices to mechanically control multicellular systems at micrometer resolution and thus mimic mechanical stresses as they occur in vivo.